Ellagic acid and cilostazol ameliorate amikacin-induced nephrotoxicity in rats by downregulating oxidative stress, inflammation, and apoptosis - Zeinab Mahmoud Saeed; Monira Ismail Khattab; Nadia Esmat Khorshid; Amal Elsayed Salem (PLoS ONE, 2022)
Amikacin (AK) has the largest spectrum of aminoglycosides. However, its use is constrained because of nephrotoxicity and ototoxicity. Ellagic acid (EA) is a polyphenol present in plants. It has antioxidant, anticarcinogenic, and antimutagenic characteristics. Cilostazol (CTZ) is a phosphodiesterase Ш inhibitor, it is a potent vasodilator and antiplatelet drug. CTZ has an inhibitory effect on reactive oxygen species and superoxide generation in addition to hydroxyl radicals scavenging action. This study determines whether EA and cilostazol have a protective effect against AK-induced nephrotoxicity. Forty-nine rats were divided into seven equal groups: control normal; AK 400 mg/kg; EA 10 mg/kg; CTZ 10 mg/kg; AK 400 mg/kg plus EA 10 mg/kg; AK 400 mg/kg plus CTZ 10 mg/kg; AK 400 mg/kg plus EA 10 mg/kg and CTZ 10 mg/kg. For seven days, drugs were administered using gavage one hour before intramuscular injection of AK. Twenty-four hours after the last AK dosage, blood samples were collected to determine blood urea nitrogen and creatinine levels. Kidneys were removed for histopathological examination and measurement of: malondialdehyde (MDA), catalase (CAT), decreased glutathione (GSH), superoxide dismutase (SOD), interleukin 6 (IL6), tumor necrosis factor-alpha (TNFα), nuclear factor kappa B (NFκB), and Bcl-2 associated x protein (BAX). AK caused kidney damage, inflammatory mediator elevation, and oxidative stress and apoptotic markers. Rats receiving EA or CTZ indicated significant improvement in kidney function, decrease in oxidative stress and inflammation through NF-kB down-regulation and BAX expression. The combination of EA and CTZ showed a synergistic effect. In conclusion, EA and CTZ might play a beneficial role in preventing nephrotoxicity induced by AK partially by inhibition of tissue inflammation and apoptosis.